Analysis of the Implementation of the Village Consultative Body (BPK) in Sakaq Tada Village, Mook Manaar Bulatn District, West Kutai Regency, Indonesia - Novita Kotjoob Raintung; B. Budiman; J. Jumansyah; Sry Reski Mulka (Golden Ratio of Mapping Idea and Literature Format, 2026)
The Village Consultative Body (BPK) is a representative institution of the community that plays an important role in village governance, particularly in discussing village regulations, channeling community aspirations, and supervising the performance of the village government. This study aims to analyze the implementation of the BPK's functions in Sakaq Tada Village, Mook Manaar Bulatn Subdistrict, West Kutai Regency, and to examine the compatibility between normative provisions and empirical practices in the field. This study uses a qualitative, descriptive-analytical approach. Data were collected through in-depth interviews, observations, and documentation of informants, including the BPK Chair and Members, Village Officials, village government officials, and the Head of the Neighborhood Association (RT). Data analysis was conducted inductively using Miles and Huberman's interactive analysis model, which includes the stages of data collection, data reduction, data presentation, and conclusion drawing. The results of the study show that normatively, the BPK has carried out its three main functions in accordance with applicable regulations. However, empirically, the implementation of these functions has not been fully optimal. The legislative function is still limited to discussing routine regulations; the supervisory function has not been carried out systematically; and the function of channeling community aspirations is often carried out through informal mechanisms. This condition is influenced by limited human resource capacity, minimal technical training, and suboptimal institutional working mechanisms at the BPK. This study concludes that strengthening the BPK's role requires increasing institutional and human resource capacity, as well as strengthening coordination between the BPK and village governments to support more effective and accountable village administration.